2019
DOI: 10.1039/c9ra08875j
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting effect of CO2 on the oxidative combustion thermodynamics of coal

Abstract: A thermal analysis experiment was conducted in O 2 /N 2 /CO 2 and O 2 /N 2 atmospheres (O 2 concentrations were 21, 14, 8, and CO 2 concentrations were 0, 39, 46, 52) to investigate the thermal behavior of coal oxidation and combustion. Results demonstrated that an elevated CO 2 concentration or decreased O 2 concentration had a delaying effect on the thermogravimetric analysis and differential scanning calorimetry (DSC) curves; moreover, the characteristic temperatures were substantially augmented.When the O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 37 publications
3
14
0
Order By: Relevance
“…The results showed that the oxidative heat evolution of pulverized coal has obvious stage characteristics of rst absorbing heat and then releasing heat. Other scholars [9][10][11][12] also came to a conclusion consistent with the above. Chang et al [13] investigated the oxidation pyrolysis of coal below 150℃ in Yangquan through a thermal analyzer.…”
Section: Introductionsupporting
confidence: 73%
“…The results showed that the oxidative heat evolution of pulverized coal has obvious stage characteristics of rst absorbing heat and then releasing heat. Other scholars [9][10][11][12] also came to a conclusion consistent with the above. Chang et al [13] investigated the oxidation pyrolysis of coal below 150℃ in Yangquan through a thermal analyzer.…”
Section: Introductionsupporting
confidence: 73%
“…In the physical simulation experiment, proper material selection would be crucial for the experiment [10,11]. With relevant simulation theory, simulation material should satisfy the simulation principle for fluid-solid coupling and other basic properties.…”
Section: Principle On Materials Selectionmentioning
confidence: 99%
“…Li et al [30] researched the macro-characteristic indexes of coal samples at different O 2 concentrations (3%, 8%, 13%, 17%, and 21%) with the temperature ranging from 30 • C to 500 • C. Ma et al [31] probed into the thermokinetic characteristics of coal samples when they were heated from 30 • C to 800 • C under the N 2 atmosphere with O 2 concentrations being 5%, 9%, 13%, 17%, and 21%, respectively. Ren et al [32] explored the thermodynamic behavior of coal sample oxidation with O 2 concentrations being 8%, 14%, and 21% under the O 2 -N 2 -CO 2 atmosphere and the O 2 -N 2 atmosphere, respectively. Zhang et al [33] studied the thermogravimetric characteristics of coal oxidation and spontaneous combustion under the N 2 atmosphere with O 2 concentrations being 5%, 12.5%, and 21%, respectively.…”
Section: Introductionmentioning
confidence: 99%